Imaging space weather over Europe. Issue 2 (25th February 2013) - Baumgardner, Jeffrey; Wroten, Joei; Mendillo, Michael; Martinis, Carlos; Barbieri, Cesare; Umbriaco, Gabriele; Mitchell, Cathryn; Kinrade, Joe; Materassi, Massimo; Ciraolo, Luigi; Hairston, Marc
Abstract : We describe the introduction of the first all‐sky imaging system for low‐light‐level optical observations of the disturbed ionosphere over mid‐latitude Europe. Using 6300 Å auroral emissions that come from the 200–400 km altitude range, we demonstrate that sub‐visual optical patterns spanning the European continent can be obtained from a single site in Italy. Pilot observations during the 26–27 September 2011 geomagnetic storm show that the diffuse aurora's low latitude boundary can be used to find where the poleward wall of the ionospheric trough is located. This relates directly to regions of radiowave disruptions caused by the precipitation of energetic particles from the magnetospheric plasma sheet that move to lower latitudes during space weather events. Images of stable auroral red (SAR) arcs can be used to track the magnetospheric ring current and plasmapause location, a second region of radiowave interference. Comparisons with ground‐based and satellite observations of the ionosphere during the same storm demonstrate how ASI images reveal the lowest energy components of magnetospheric input to the ionosphere‐thermosphere system. Such observations can be used, potentially, for both now‐casting of storm effects spanning Europe, and for retrospective validation of existing models of space weather impacts at sub‐auroral locations. Key Points: First use of an all‐sky airglow imager in mid‐latidude Europe Optical emission boundaries describe locations of plasma structures Radio propagation impacts mapped over regions spanning ~million sq. km